Morphological Variations in Human Liver: A Cadaveric Study - Mansur, Dil Islam; Shrestha, P; Maskey, S (Nepal Medical College Journal, 2019)
The variations of liver like the accessory fissures and lobes are a potential source of diagnostic errors. The knowledge in the variations may help in diagnosis, treatment planning and minimize the risk of post operative complications. The present study was aimed to observe the morphological variations of livers. The study was done in 70 formalin fixed human livers and was observed for morphological variations. The present study concluded the normal morphology of liver was in 54.28% and anomalies in 45.71% of liver. The most common anomalies were accessory fissures which were found in 32.86% of livers. The second common anomalies were absence or incomplete fissure for ligamentum teres in 15.71% of livers. Then the enlarged papillary process was found in 11.43%, short gall bladder was in 10% and elongated left lobe was in 7.14%. The knowledge of normal and variant liver may contribute to the understanding of the liver disease and to achieve correct preoperative diagnosis; and to avoid intra-operative complications.